Teleporting what matters [quantum computing]. - Hellemans, A. (IEEE spectrum)
Physicists in Austria and the US have shown for the first time how to teleport the properties of one atom to another. At the National Institute of Standards and Technology, a team of teleporters trapped three beryllium ions. The ions - beryllium atoms with missing electrons and hence a positive charge - are subjected to forces from electric fields so that they can be held in an ion trap. Here, radio waves and electric fields from a set of electrodes hold the ions in a line but also allow them to be moved from one segment of the trap to the other. This way, ions could be brought over to the different laser beams used for entanglement and for the measurement of quantum states. Two atoms can be entangled by simultaneously undergoing changes in quantum state when hit with a specific series of laser pulses. The same teleportation protocol was used by another team at Innsbruck University. However, this team used a different type of trap, one with no segments. Instead of moving the ions to the lasers, the team was able to aim the lasers well enough so that they could move the laser beams to the ions. These simple trap systems have been found to be very promising and may first be applied in a specialized computer called quantum repeater. This kind of device, though still the stuff of mere theory, would extend the range of wiretap-proof quantum communication systems that encode messages in the polarization of photons.